Santri's perception of cigarettes on smoking behavior in Lirboyo Islamic Boarding School, East Java - Renny Nurhasana; Ni Made Shellasih; Danty Novitasari; Suci Puspita Ratih (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Indonesia Basic Health Research Data in 2018 shows that smokers in the 10-18 years age group increased to 9.1%. The phenomenon of smoking in adolescents in Indonesia has touched on educational institutions such as pesantren, where students are found to have smoked from an early age. This study aims to review the influence of students' perceptions of cigarettes based on smoking habits, cigarette advertisements and the image of cigarette companies to the smoking behaviour in students at Lirboyo Islamic Boarding School. This research is a quantitative study with a cross-sectional study design using 40 students as research samples. We use modified structured questionnaire from the Smoke-Free Agents. Research shows 62.5% of students are active smokers. Based on the bivariate test, we found a relationship between perceptions of smoking habits and perceptions of cigarette advertising (p-value <0.05) to the smoking behaviour. In addition, we found that there is no relationship to the perception of the image of the cigarette company (p-value> 0.05). This study found a high percentage of students who smoked in the Lirboyo Islamic Boarding School. Students' perceptions of smoking habits and students' perceptions of cigarette advertisements are related to students' smoking behaviour. The denormalization of cigarette products needs to be carried out by Islamic Boarding School Management to control smokers among students and prevent adolescent’s smoker.